THE LIFE AND WORK OF ULUGBEK MUSAEV, AN HONORED ARTIST OF UZBEKISTAN, AND COMPOSER NABIEV ABDUSAID - Madaminovna, Karimova Mavlyuda (FAN, TA’LIM VA AMALIYOT INTEGRATSIYASI, 2022)
This article covers the life and work of Ulugbek Musaev, a distinguished artist of Uzbekistan, winner of the Republic State Prize, and composer Nabiev Abdusaid.